Changes in patient background and prognosis after hepatectomy for hepatocellular carcinoma by hepatitis virus infection status: New trends in Japan - Yukiyasu Okamura; Teiichi Sugiura; Takaaki Ito; Yusuke Yamamoto; Ryo Ashida; Katsuhisa Ohgi; Shimpei Ohtsuka; Takeshi Aramaki; Katsuhiko Uesaka (Annals of Gastroenterological Surgery, 2021)
Abstract Aim Hepatitis C virus (HCV) infection is a major cause of hepatocellular carcinoma (HCC) in Japan. However, the cause and prognosis of HCC may be dramatically changed by direct acting antiviral agents (DAAs). Although the 2015 nationwide survey used a large cohort, its findings may be outdated. The present study therefore aimed to show the latest outcomes by patients’ hepatitis virus infection status. Methods We included 552 patients who underwent hepatectomy for primary HCC between 2002 and 2018 and compared clinical factors between those treated before 2014 (n = 380) and after 2014 (n = 172), when DAAs became available. Results Distribution of hepatitis virus infection status between the two groups differed significantly (P < 0.001). In the earlier group, 46% of the patients had HCC with HCV infection (C‐HCC), whereas the rate of C‐HCC decreased (31%) and 54% of the patients had HCC with no hepatitis virus infection (NBNC‐HCC) in the latter group. The proportion of HCC with hepatitis B virus infection (B‐HCC) and the prognosis of B‐HCC did not significantly change between the two groups. Among patients with C‐HCC, the latter patients had significantly longer relapse‐free survival (RFS) than the earlier patients (P = 0.033). However, RFS did not significantly differ between the earlier and latter patients with NBNC‐HCC. Conclusion Postoperative prognosis has changed according to patients’ hepatitis virus infection status. The proportion of patients with NBNC‐HCC has increased, but their prognosis has not been improved. Treatment strategies for NBNC‐HCC should be established.